The Effect of Service Quality on Customer Satisfaction in Purchasing Maryam Ibu Bread in Makassar - Nur Faradillah Marzettih Askari; Anwar; Muhammad Ilham Wardhana Haeruddin; Muh. Ichwan Musa; Zainal Ruma (Lafadz Jaya Publisher, 2023)
This study aims to analyze the effect of service quality on consumer satisfaction of Roti Maryam Ibu. The variables in this study are service quality (X) and customer satisfaction (Y). The method used in this study uses quantitative methods. Data collection techniques in this study used questionnaire media with the Likert method. The population in this study are customers from Roti Maryam Ibu. The sampling technique uses the Lemeshow formula with a sample of 88 consumers. The data analysis method used is descriptive analysis and simple linear regression analysis using SPSS to see the effect of the independent variables on the dependent variable, the significance value of the service quality variable is obtained at 0, 00 indicates that the independent variable has a positive and significant effect on the dependent variable with a significance value of 0.00 <0.05. This study shows that the service quality variable has a positive coefficient regression direction with customer satisfaction. The results of the analysis show that there is an influence of service quality on customer satisfaction.